Potret Publisitas Universitas Gadjah Mada - , FARIDA YULIANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Publicity is an integral part in the effort to shape the image then building the reputation of an organization. Therefore it is important to create a good publicity as well as to always monitor and evaluate it regularly in order to make the organization gaining a better position in the eyes of the public. This study tended to describe the publicity of UGM, which covered the planning and implementation of the publicity planning to the being uploaded to the media, as well as the reflection over the publicity The method to data collection used in this descriptive study was in-depth interview. In general, it resulted that Bidang Humas as task force unit for public relation in UGM has conducted the publicity function which covered the planning and implementation of the planning. However Bidang Humas has not yet conduct a proper evaluation towards its activities, including in the matter of publicity. The evaluation on publicity which conducted by Bidang Humas UGM until now was in form of media monitoring by clipping the news articles in printed media which reporting the news on UGM. The organization structure of the internal Bidang Humas which in less ideal form became one of the reasons behind the inaccessibility of the evaluation. In the last three years, the number of news reporting on UGM in the printed media was decline. This study result could be used as an early warning for Bidang Humas to conduct more proper evaluation towards publicity of UGM, as well as to discover the potential in making the next policies.